Meritocracy in Public Sector Governance: Challenges And Policy Solutions in Ogan Komering Ulu - Dwiputrianti, Septiana; Utama, Aditya Bima Hendra; Listiani, Teni; Rahman, Abdul (Jurnal Administrasi dan Kebijakan Publik, 2024)
Toward implementing a meritocratic approach in public sector management, Ogan Komering Ulu Regency faces critical challenges in adopting a merit-based system for managing civil servants (ASN). This study explores the policy application and obstacles in achieving meritocracy within the local government context. Employing a qualitative methodology, including in-depth interviews and document analysis, the research identifies key issues in the system's implementation. Findings indicate that despite efforts to establish fair and competency-based management, several challenges persist, such as limited resources, political influence, and gaps in stakeholders' understanding. These factors hinder the full adoption of the merit system, affecting the effectiveness and professionalism of public administration. The study suggests that for optimal implementation, local governments need to bolster strategic leadership, allocate adequate resources, and continuously enhance civil servants' capacity through training and development initiatives. This research contributes to the discourse on meritocracy in public administration, offering insights into necessary improvements to promote fair and transparent governance based on merit.